Association of Hypertriglyceridemia with Ischemic Stroke, Study in a Tertiary Care Hospital in Bangladesh (Journal of Medicine, 2016)
Background: Hypertriglyceridemia fosters the development of atherosclerosis via several mechanisms and lead to ischemic stroke (IS) through its contribution to thrombogenicity. The association of hypertriglyceridemia with ischemic stroke was evaluated in this study.Methods: This was a case control study conducted in the Department of Medicine, Dhaka Medical College Hospital and data was collected in a questionnaire from January to June2013. Patients presented with ischemic stroke, confirmed by CT scan of Head/ MRI of brain from 1 day to 6 months and other than ischemic stroke patients were considered as case and control respectively.Results: The mean age was found 61.0±8.3 years in case group and 60.5±8.1 years in control group. Male were predominant in both groups which was 80 (80.0%) in case group and 84 (84.0%) in control group. More than two third (68.0%) in cases and one fourth (25.0%) in controls patients had hypertension. 12 (12.0%) in cases and 2 (2.0%) in controls patients had heart disease. Normal triglycerides was found 52 (52.0%) in cases and 72 (72.0%) in control. The mean TG was found 179.9±62.8 mg/dl in cases and 148.0±51.9 mg/dl in controls. Desirable cholesterol was found 16 (16.0%) in cases and 25 (25.0%) in controls. The mean cholesterol was found 238.0±4.0 mg/dl in cases and 213.0±42.0 in controls. Optimal LDL was found 12 (12.0%) and 18 (18.0%) in case and control group respectively. Mean LDL was found 167.0±35.2 mg/dl in cases and 141.0±36.1 mg/dl in controls. Low HDL was found 64 (64.0%) in cases and 26 (26.0%) in controls. Mean HDL was found 41.2±10.6 mg/dl in case group and 49.0±8.6 mg/dl in control group.Conclusion: Ischemic stroke is significantly associated with a higher level of TC, TG, LDL and HDL (inversely). Therefore, Hypercholesterolemia and Hypertriglyceridemia may be a risk factor for ischemic stroke.J MEDICINE January 2016; 17 (1) : 21-26